Compact Ultra Wide Band Microstrip Bandpass Filter Based on Multiple-Mode Resonator and Modified Complementary Split Ring Resonator. (4th November 2013) - Marcotegui, J. Antonio; Illescas, Jesús Miguel; Estevez, Aritz; Falcone, Francisco
Abstract : A new class of broadband microstrip filters for Ultra Wide Band (UWB) applications is proposed. In the design, different stages of parallel-coupled microstrip line and other stages with a Modified Complementary Split Ring Resonator (MCSRR)—a concept proposed here for the first time—are adjusted to obtain the desired response with broadband, sharp rejection, low insertion loss, and low return loss. Full wave simulation results as well as measurement results from fabricated prototypes are presented, showing good agreement. The proposed technique offers a new alternative to implement low-cost high-performance filter devices, applicable to a wide range of communication systems.